Validation of a thermal elastohydrodynamic multibody dynamics model of the slipper pad by friction force measurement in the axial piston pump. (November 2017) - Hashemi, Sohil; Friedrich, Hendrik; Bobach, Lars; Bartel, Dirk
Abstract: The friction force between one slipper pad and swash plate is measured from a newly developed axial piston pump. This developed pump has common axial piston pump kinematics and loads acting on slipper pad. The pump allows the measurement of the friction force on the swash plate applied by one slipper pad only and the pressure in the piston chamber. The measurement results, taken from several test rig trails are presented and discussed here. The experiments are simulated by a thermal elastohydrodynamic multibody dynamics model of the slipper pad and swash plate considering mass conserving cavitation, non-Newtonian flow and a mixed friction model based on real-measured surface topologies. The simulated friction forces show a good agreement with the measurements. Highlights: Presentation of a newly developed axial piston pump which allows the measurement of slipper pad friction force in the pump. Friction force measurement between slipper pad and swash plate in the pump for four slipper pads differing in slipper design. Validation of calculated friction force by a thermal elastohydrodynamic multibody dynamics model of the slipper pad. Simulated friction force shows a good agreement with measurements.